Sosialisasi Dan Workshop Aplikasi Berikan-Jambi Sebagai Media Binaan Manajemen Konservasi Ikan Lubuk Larangan Guci Emas Pada Desa Muara Pijoan - Sukmono, Tedjo; Utomo, Pradita Eko Prasetyo; Wulandari, Tia; Hutabarat, Benedika Ferdian; Suprayogi, Dawam (Jurnal Pengabdian Masyarakat Pinang Masak, 2025)
In community life, cultural elements play a crucial role as guidelines for social order. The culture applied in society extends beyond objects to behavior, attitudes, attitudes toward nature, and even the management of nature itself. One of Jambi Province's abundant natural resources is its fish biodiversity. The Batanghari River has a significant impact on both fish diversity and culture. This cultural connection to fish remains deeply embedded in the community to this day. Furthermore, fish folklore is also found, which is beneficial for fish conservation. Ethnoscience is not merely a cultural knowledge; it is also an intangible heritage of Jambi Province. Therefore, ethnoscience and fish biodiversity are interconnected. Ethnoscience and fish biodiversity are now integrated into a single information system, the Jambi Fish Biodiversity Information System (BERIKAN JAMBI) https://ikanjambi.unja.ac.id/. This integrated information system contains information about the fish found in the Batanghari River. The socialization and application workshop given to the Guci Emas awareness group in Muaro Pijoan Village aims to provide knowledge and understanding regarding the Berikan Jambi information system in supporting ethnoscience studies of the community in the area and as a conservation step through the fostered group, so that it can make it easier for the community to obtain information about local folklore regarding certain fish.